Faktor Risiko Terjadinya Penyakit Jantung Koroner pada Pasien di Unit Rawat Jalan Rumah Sakit Panti Rapih Yogyakarta - Deviana Widayanti; Chatarina Setya Widyastuti (STIKes Panti Rapih, 2020)
Background: Coronary Heart Disease (CHD) Is a condition when the arteries that supply blood to the heart wall experience hardening and narrowing. It is estimated that 30% of coronary heart disease causes death worldwide. Objective: This study aims to determine the risk factors for CHD in Panti Rapih Hospital. Methods: This descriptive study aims to determine the risk factors for CHD in outpatients at Panti Rapih Hospital. The population is patients who have been diagnosed with coronary heart disease and the sample was taken by 50 respondents with non-random accidental sampling technique. This research take the data use questionnaire and make univariat analysis. Results: Risk factors for CHD are a number of factors that cannot be changed: family history of 42%, age = 40 years 95% in men and 95% age = 65 years in women. Factors that can be changed are: Smoking 78%, history of hypertension 68%, history of diabetes mellitus 28%, dyslipidemic 90%, excess body weight42% and lack of exercise 38%. Conclusion: Risk factors for CHD that cannot be changed: family history of 42%, age = 40 years 95% in men and 95% age = 65 years in women. Factors that can be changed are: Smoking 78%, history of hypertension 68%, history of diabetes mellitus 28%, dyslipidemic 90%, excess body weight 42% and lack of exercise 38%. Keywords: coronary heart disease, risk factors